Effect of magnetized water on the fundamental grouting properties of cement grout under varying magnetization conditions - Chao Deng; Liuxi Li; Huanxiao Hu; Zhichao Xu; Yi Zhou; Quan Yin; Juan Chen (Scientific Reports)
Abstract The development and modification of grouting materials constitute crucial factors influencing the effectiveness of grouting. Given the pivotal role of water in the hydration of cement-based composite materials and construction processes, this study proposes an exploratory approach using green, economical magnetized water technology to enhance the performance of cement grouts. The research systematically investigates the effects of magnetized water on the fundamental grouting properties (stability, rheological behavior, and stone body strength) of cement grouts, prepared under varying magnetization conditions (including magnetic intensity, water flow speed, and cycle times). Through the conduct of specific physicochemical tests on water, the study elucidates the mechanism through which magnetized water influences these properties. The results indicate that magnetized water positively impacts the stability of cement grouts, significantly reducing their absolute viscosity, apparent viscosity, plastic viscosity, and yield stress, thus markedly affecting the rheological characteristics of the cement grouts. Additionally, magnetized water notably enhances the flexural and compressive strength of the cement grout stone body, with a particularly significant improvement in early strength. From a quantum mechanics perspective, a magnetization mechanism based on the competition between the strengthening of hydrogen bonds between water molecule clusters and the weakening or breaking of hydrogen bonds within clusters is introduced, providing a theoretical basis for explaining the variability observed in water magnetization experiments.